Community Participation to Support Sustainable Settlement and Economic Development (Global Journal of Science Frontier Research, 2015)
Housing is complex sector and become a basic human need. Therefore, policies on housing directly impacts people's lives. Lately sustainable housing policy into trends and new requirements to prevent greater damage on Earth. Each policy requires public support to make it happen. The concept of sustainable housing related to environmental, social, economic, and cultural aspects. The purpose of this research is to understand activity of environmentally friendly by residents of kampung and its benefits in the economic field. This study will focus on the environmental and economic aspects. Selected case studies is a village that ever won an awards of green and clean from Surabaya city government, This kampung has succeeded in creating an environment beautiful and well cared for, also received economic benefit of the activity. The method used in this research is descriptive qualitative comparative analysis. The study examined the causes of the condition and explain it with words.
Keywords: economic development; participation; sustainable housing